Schema therapy : distinctive features - Rafaeli, Eshkol, 1970-; Bernstein, David P.; Young, Jeffrey E., 1950- (Hove, East Sussex : Routledge, 2011)
Schema therapy combines proven cognitive behaviour therapy techniques with elements of interpersonal, experiential and psychodynamic therapies in order to help people with long term mental health problems including personality disorders and chronic depression. Schema therapy suggests that many negative cognitive conditions are based on past experiences, and therefore provides models for challenging and modifying negative thoughts and behaviours in order to provoke change. In this book, Jeffrey Young, Eshkol Rafaeli, and David Bernstein - pioneers of the schema therapy approach - indicate the 30 distinctive features of schema therapy, and how the method fits into the broader CBT Spectrum. Divided into two sections The Distinctive Theoretical Features of Schema Therapy and The Distinctive Practical Features of Schema Therapy, this book will provide a concise introduction for those new to the technique, as well as a discussion of how it differs from the other cognitive behavioural therapies for those experienced in the field
Includes bibliographical references and index
Keywords: Schema-focused cognitive therapy; Cognitive therapy -- methods; Mental disorders -- Therapy